Descriptors and graphical construction for in silico design of efficient and selective single atom catalysts for the eNRR. Issue 34 (16th August 2022) - Kapse, Samadhan; Narasimhan, Shobhana; Thapa, Ranjit
Abstract : Outline a screening protocol that uses density functional theory calculations to simultaneously optimize with respect to multiple criteria, thereby successfully identifying catalysts that are highly selective and also result in low overpotentials for ammonia production through eNRR. Abstract : The electrochemical nitrogen reduction reaction (eNRR) offers the possibility of ammonia synthesis under mild conditions; however, it suffers from low yields, a competing hydrogen evolution reaction pathway, and hydrogen poisoning. We present a systematic approach toward screening single atom catalysts (SACs) for the eNRR, by focusing on key parameters computed from density functional theory and relationships between them. We illustrate this by application to 66 model catalysts of the types, TM-Pc, TM-N X C Y, and TM-N3, where TM is a 3d transition metal or molybdenum. We identified the best SACs as Sc-Pc, Cr-N4, Mn-Pc, and Fe-N2 C2 ; these show eNRR selectivity over the HER and no hydrogen poisoning. The catalysts are identified through multi-parameter optimization which includes the condition of hydrogen poisoning. We propose a new electronic descriptor Oval, the valence electron occupancy of the metal center that exhibits a volcano-type relationship with eNRR overpotential. Our multi-parameter optimization approach can be mapped onto a simple graphical construction to find the best catalyst for the eNRR over the HER and hydrogen poisoning.